Theoretical study on plasmonic applications of Gallium alloy (GaX, X = Ag, Al, Hg and In) nanospheres and nanoshells. (April 2022) - Bhardwaj, Akanksha; Verma, S.S.
Highlights: The Gallium alloys (GaAg, GaAl, GaHg and GaIn) as core-shell nanosphere are studied. Plasmonic properties and absorption efficiencies are observed to search alternatives to widely used Gallium-indium alloy. Plasmonic spectra are tuned over UV-Visible region of EM spectrum by controlling the core and shell size. This study provides applications of Gallium alloys in soft antennas, energy harvesting applications and in liquid motors coated with rigid shell as wheeled robots. Abstract: Gallium (Ga) being easily morphed due to its soft matter texture and having high electronegativity is widely researched metal in the world of plasmonics. Liquid metal (LM) alloys in the form of spheres (dense) and hollow shell nanostructures has the potential to provide more functionality and enhanced sensitivity to their optical properties. The optical properties can further be increased by using Ag coatings on these liquid nanostructures with an increased stability towards oxidation and shape formation. We here theoretically study Ga alloys (GaAg, GaAl, GaHg and GaIn) observing their plasmonic properties and absorption efficiencies to search alternatives to widely used Gallium-indium alloy. Mie theory is used which provides the exact calculations of plasmon induced optical properties of nanoparticles (NPs). The optimized size of these complex nanostructures is discussed along with their potential applications. The broad band absorption is shown between 100 to 400 nm, and the peak values are tuned by size and shell thickness factor. The maximum absorption efficiency of 4.57 is observed for GaAg LM alloy.